“After all the traumas my body has been through, I feel good that it is still working.” – Basic Body Awareness Therapy for traumatised refugees - Carlsson, Jessica; Stade, Kajsa; Skammeritz, Signe; Hjortkjær, Charlotte (Torture Journal, 2018)
Basic Body Awareness Therapy (BBAT) is a form of physiotherapy that is often used for psychiatric patients in Scandinavian countries. To our knowledge, there have not been any studies investigating BBAT as a treatment for traumatised refugees until now. Objective: To explore the compliance, acceptability and treatment satisfaction using group BBAT in traumatised refugees. To study changes in psychiatric and somatic symptoms as well as the quality of life, level of functioning and quality of movement during treatment with BBAT. Method: All Arabic speaking patients that previously had received treatment at the Competence Centre for Transcultural Psychiatry in Copenhagen from April 2008 to June 2009 were invited to participate (N=29). Nine persons were included in a male (N=4) and female (N=5) group. All participants were traumatised refugees. The BBAT treatment consisted of 14 sessions over a period of 14 weeks. Before and after treatment the participants were interviewed using a semi-structured interview guide. The interviews were transcribed and analyzed with a thematic approach. The participants also filled out self-administrated questionnaires and two physiotherapists tested the participants’ movement harmony using the Body Awareness Rating Scale-Movement Harmony (BARS-MH) test. At the end of the study, the participants filled out anonymous questionnaires about treatment satisfaction. Results: The results showed that the participants had a high compliance, acceptability and treatment satisfaction with BBAT. The majority of participants showed improvements in symptoms from baseline to post-intervention on the self-administrated questionnaires and in the BARS-MH test. Conclusions: Further research is needed to expand the scientific knowledge regarding the use of BBAT in traumatised refugees. If future research can confirm our positive findings it will have a considerable impact on future treatment designs and for the individual patient.